(untitled) (Revista do Centro de Estudos Portugueses, 2006)
Este ensaio analisa comparativamente a novela A confissão de Lúcio, do português Mário de Sá-Carneiro, e o romance O retrato de Dorian Gray, do irlandês Oscar Wilde, focalizando as discussões éticas e estéticas por eles veiculadas, sobretudo no que se refere à questão pós-moderna da supremacia do ego sobre a obra de arte. This essay analyses comparatively the novel Lucio’s confession, written by the portuguese Mário de Sá-Carneiro, and the novel The portrait of Dorian Gray, written by the irish Oscar Wilde, focalizing the aspects discussed by them, specially the ones related to the postmodernist question of the supremacy of the ego over the artwork.